Application of the Principle of Determinism in the Historical Sciences - Meškauskas, Eugenijus (Problemos, 1986)
The article deals with the peculiarities of application of the principle of determinism in the historical sciences. The author concludes that the principle can be directly applied only in the analysis of interrelations between economic structure of society and material conditions of its existence. The other parts of social development are bound to deterministic explanation only in the aspect of their functional relations to economic structure. In any case, the object of deterministic explanation is objective results of man’s activity and not his will.